Observer-based event-triggered control in the presence of cone-bounded nonlinear inputs. (August 2019) - Moreira, L.G.; Tarbouriech, S.; Seuret, A.; Gomes da Silva Jr., J.M.
Abstract: This paper presents an observer-based event-triggered strategy for linear systems subject to input cone-bounded nonlinearities. Both the emulation and co-design problems are addressed. Considering a Lyapunov approach and the cone-bound property of the input nonlinearity, sufficient conditions based on linear matrix inequalities are derived to ensure regional or global asymptotic stability of the origin of the closed-loop system. These conditions are incorporated into convex optimization problems to optimally determine the event generator parameters and the controller gain (in the co-design case) aiming at reducing the number of control updates with respect to periodic implementations for a prescribed observer gain. The event-triggering strategy considers a dwell time to cope with Zeno behaviors. Numerical examples, considering systems with quantized logarithmic inputs and saturating inputs, illustrate the potentialities of the approach.